Hematology and serum chemistry in stranded and wildcaught harbor seals in central California:Reference intervals, predictors of survival, and parameters affecting blood variables - Greig, Denise J.; Gulland, Frances M.D.; Rios, Carlos A.; Hall, Ailsa J. (Journal of Wildlife Diseases, 2010)
Blood was collected from stranded harbor seal (Phoca vitulina) pups at admission (n=64) and release (n=45) from rehabilitation in 2007 and 2008 and from wild-caught harbor seal pups, subadults, and adults (n=110) in 2004, 2007, and 2008. Blood values measured at the time of admission were not predictive of survival during rehabilitation. Mass was associated with survival until release, and all pups that died weighed less than 10 kg at the time of admission. Dohle bodies were observed in leukocytes from 15% to 22% of the pups in rehabilitation, but not in the wild pups. Thresholds (95% confidence intervals) among wild pups were less than those in the released pups for leukocytes, neutrophils, total cholesterol, alanine aminotransferase (ALT), glucose, phosphorus, sodium, potassium, total protein, albumin, and globulin; thresholds were greater in wild pups than in released pups for hemoglobin (HGB), hematocrit (HCT), and glucose. Thresholds among released pups were less than those in wild pups for HGB, HCT, mean cell volume, chloride, and creatine kinase; thresholds among released pups were greater than those in wild pups for neutrophils, platelets, total cholesterol, triglycerides, ALT, aspartate aminotransferase, sorbitol dehydrogenase, bilirubin, phosphorus, potassium, total protein, and albumin. Age, girth, and geographic location affected the blood variables from wild-caught pups; age class, geographic location, sex, and body condition affected the blood variables of wild-caught, subadult and adult harbor seals.